Pupal stages of three species of the phytophagous genus Merodon Meigen (Diptera: Syrphidae) - Preradović, Jelena; Andrić, Andrijana; Radenković, Snežana; Zorić, Ljiljana Šašić; Pérez-Bañón, Celeste; Campoy, Andrés; Vujić, Ante (Zootaxa, 2018)
plants, are mostly unknown. All known immature stages of Merodon feed on underground storage organs (bulbs, rhizomes and corms) of geophytes of the families Asparagaceae, Iridaceae and Amaryllidaceae. Of 160 known Merodon species, to date, the pupal stages have been described for only four: M. equestris (Fabricius), M. bombiformis Hull, M. luteihumerus Marcos-García, Vujić & Mengual, and M. geniculatus Strobl. During field investigations in Đerdap National Park, Serbia, Merodon puparia were found in the ground near the bulbs of Ornithogalum umbellatum L. (Asparagaceae). DNA barcoding revealed that they belonged to the species M. aureus Fabricius and M. avidus (Rossi). Analysis of museum material from the Bavarian State Collection of Zoology in Germany revealed the puparium of an additional species, M. rufus Meigen. In our study we provide for the first time descriptions of the puparia of these three Merodon species. The main diagnostic morphological characters of the pupal spiracles and posterior respiratory processes are described using scanning electron microscopy, and cephalopharyngeal skeletons using binocular microscopy. In addition, puparium morphology of M. aureus, M. avidus and M. rufus is compared with known puparia of four other Merodon species and with the third larval stage of M. hurkmansi Marcos-García, Vujić & Mengual.